How many receptor-like kinases are required to operate a pollen tube - Muschietti, Jorge Prometeo (2017)
Successful fertilization depends on active molecular dialogues that the male gametophyte can establish with the pistil and the female gametophyte. Pollen grains and stigmas must recognize each other; pollen tubes need to identify the pistil tissues they will penetrate, follow positional cues to exit the transmitting tract and finally, locate the ovules. These molecular dialogues directly affect pollen tube growth rate and orientation. Receptor-like kinases (RLKs) are natural candidates for the perception and decoding of extracellular signals and their transduction to downstream cytoplasmic interactors. Here, we update knowledge regarding how RLKs are involved in pollen tube growth, cell wall integrity and guidance. In addition, we use public data to build a pollen tube RLK interactome that might help direct experiments to elucidate the function of pollen RLKs and their associated proteins.